Democracy in Bangladesh : political dimensions of national development : selected papers from the 2008 and 2009 conferences on Bangladesh at Harvard University - Khan, Zillur R. (Zillur Rahman), 1938-; Andaleeb, Dr. Syed Saad (University Press Limited, 2011)
Contributed papers presented at the conferences organized by Bangladesh Development Initiative along with Democracy and Development in Bangladesh Forum and The Ash Institute for Democratic Governance & Innovation, held at John F. Kennedy School of Government at Harvard University.